From grab and go to engaging communities in language research - Stefanie Pillai (Proceedings of AICS - Social Sciences, 2017)
In many cases, language researchers collect data from community of speakers and then go on to write their theses, academic articles book, and present at conferences. The benefit of the research to these communities is often minimal. There is often no social obligation for researchers to give back to communities via knowledge-sharing activities. This leaves a large gap in the process of language research as the research findings have little or no impact on the communities concerned. This paper discusses (i) shifting the ‘grab-and-go’ research approach to one that incorporates knowledge sharing and community engagement; (ii) ways in which researchers can engage communities to help them to document, preserve and revitalize their language drawing on specific examples of the cycle of language research, documentation and revitalization of Malacca Portuguese Creole.